The safe development paradox: An agent-based model for flood risk under climate change in the European Union. (January 2020) - Haer, Toon; Husby, Trond G.; Botzen, W.J. Wouter; Aerts, Jeroen C.J.H.
Highlights: We include safe development paradox dynamics in flood risk analysis. Flood protection by governments can reduce inclination of residents to protect. Steering households towards rational behaviour can increase protective efforts. Abstract: With increasing flood risk due to climate change and socioeconomic trends, governments are under pressure to continue implementing flood protection measures, such as dikes, to reduce flood risk. However, research suggests that a sole focus on government-funded flood protection leads to an adverse increase in exposure as people and economic activities tend to concentrate in protected areas. Moreover, governmental flood protection can reduce the incentive for autonomous adaptation by local households, which paradoxically results in more severe consequences if an extreme flood event occurs. This phenomenon is often referred to as the 'safe development paradox' or 'levee effect' and is generally not accounted for in existing flood risk models used to assess developments in future flood risk under climate change. In this study we assess the impact of extreme flood events for the European Union using a large-scale agent-based model (ABM). We quantify how the safe development paradox affects (1) population growth and the increase in exposed property values, (2) the reduction in investments to flood-proof buildings as public protection increases, and (3) the increase in potential damage should a flood occur. For this analysis, we apply an ABM that integrates the dynamic behaviour of governments and residents into a large-scale flood risk assessment framework, in which we include estimates of changing population growth. We find that the impact of extreme flood events increases considerably when governments provide high protection levels, especially in large metropolitan areas. Moreover, we demonstrate how policy that stimulates the flood-proofing of buildings can largely counteract the effects of the safe development paradox.